Efektivitas Pelatihan Kurikulum Merdeka Berbasis Komunitas terhadap Peningkatan Kinerja Madrasah di Sumatera Utara - Lubis, Mohammad Halomoan (Tatar Pasundan: Jurnal Diklat Keagamaan, 2025)
This study aims to describe the effectiveness of the Community-Based Independent Curriculum Implementation (IKM-BK) Training Model in improving Madrasah performance. The research employs a qualitative-descriptive approach. Data were collected through questionnaires, interviews, and participatory observations, and analyzed descriptively using frequency tables. In general, the IKM-BK training model has proven effective in enhancing madrasah performance, particularly in terms of collaboration, community partnership, and the availability of updated curriculum-related documents aligned with the Independent Curriculum. The training has also successfully facilitated and accelerated the scaling out of training to mentored madrasahs, proving to be more effective than traditional, non-community-based training models. However, the training model appears less effective in addressing teachers' resistance to changing and adapting their teaching habits in classrooms. Using a 4-point scale for each aspect of madrasah performance, the training was found to have the greatest impact on the availability of curriculum-related documents for teachers and madrasahs, with an average score of 3.66. Meanwhile, the lowest impact was observed in classroom teaching changes, with an average score of 3.44, indicating resistance to curriculum changes despite training and mentoring efforts.  Among the four supporting elements, the participation levels were as follows: lecturers (75%), educational staff from Penmad (87%), supervisors (98%), and widyaiswara (100%). A total of 81% of target madrasahs successfully completed the assigned products, which was largely attributable to the efforts of the mentors and the support of madrasah leadership. Additionally, 75% of madrasahs participating in IKM-BK training successfully scaled out the training to their mentored madrasahs. A total of 485 private madrasahs received scaled-out training from the communities of trained madrasahs. Keywords : curriculum; effectiveness;training; community-based